Reliance on social security benefits by Swedish patients with ill-health attributed to dental fillings: a register-based cohort study - Naimi-Akbar Aron; Svedberg Pia; Alexanderson Kristina; Ekstrand Jan; Sandborgh-Englund Gunilla (BMC, 2012)
Abstract Background Some people attribute their ill health to dental filling materials, experiencing a variety of symptoms. Yet, it is not known if they continue to financially support themselves by work or become reliant on different types of social security benefits. The aim of this study was to analyse reliance on different forms of social security benefits by patients who attribute their poor health to dental filling materials. Methods A longitudinal cohort study with a 13-year follow up. The subjects included were 505 patients attributing their ill health to dental restorative materials, who applied for subsidised filling replacement. They were compared to a cohort of matched controls representing the general population (three controls per patient). Annual individual data on disability pension, sick leave, unemployment benefits, and socio-demographic factors was obtained from Statistics Sweden. Generalized estimating equations were used to test for differences between cohorts in number of days on different types of social security benefits. Results The cohort of dental filling patients had a significantly higher number of days on sick leave and disability pension than the general population. The test of an overall interaction effect between time and cohort showed a significant difference between the two cohorts regarding both sick leave and disability pension. In the replacement cohort, the highest number of sick-leave days was recorded in the year they applied for subsidised replacement of fillings. While sick leave decreased following the year of application, the number of days on disability pension increased and peaked at the end of follow-up. Conclusions Ill health related to dental materials is likely to be associated with dependence on social security benefits. Dental filling replacement does not seem to improve workforce participation.